Single Cortical Microinfarcts Lead to Widespread Microglia/Macrophage Migration Along the White Matter. (21st September 2020) - Lubart, Alisa; Benbenishty, Amit; Har-Gil, Hagai; Laufer, Hadas; Gdalyahu, Amos; Assaf, Yaniv; Blinder, Pablo
Abstract: Loss of cognitive function with aging is a complex and poorly understood process. Recently, clinical research has linked the occurrence of cortical microinfarcts to cognitive decline. Cortical microinfarcts form following the occlusion of penetrating vessels and are considered to be restricted to the proximity of the occluded vessel. Whether and how such local events propagate and affect remote brain regions remain unknown. To this end, we combined histological analysis and longitudinal diffusion tensor imaging (DTI), following the targeted-photothrombotic occlusion of single cortical penetrating vessels. Occlusions resulted in distant tissue reorganization across the mouse brain. This remodeling co-occurred with the formation of a microglia/macrophage migratory path along subcortical white matter tracts, reaching the contralateral hemisphere through the corpus callosum and leaving a microstructural signature detected by DTI-tractography. CX3CR1-deficient mice exhibited shorter trail lengths, differential remodeling, and only ipsilateral white matter tract changes. We concluded that microinfarcts lead to brain-wide remodeling in a microglial CX3CR1-dependent manner.